The Body as Medium - Embodied Communication and Body Issues in Cloud Fitness - Ma, Yuxin (International Journal of Social Sciences and Public Administration, 2024)
The "body turn" of "cloud fitness" has brought a new theoretical logic to communication. In this paper, we make a preliminary attempt at embodied communication in the context of the new Crown pneumonia epidemic, exploring the issues of body movement and moving bodies on "Shake" and "b-station". Here, the author argues that understanding embodied communication is inseparable from reflecting on technology, and that it is a form of communication in which people, media and technology interact. The article explores the changes of the philosophical category of bodily action in the virtual space of the Internet by tracing the origins of embodied communication; then understands the communication of the body as a medium through the "cloud space" and "cloud body"; and in the whole process of communication, the physical attributes of the body give the online and offline behaviors of the body a new meaning and a new meaning and a new meaning. In the whole process of communication, the physical attributes of the body bring tension to the online and offline actors; in the future, with the advent of the scene-oriented era, the body will have multiple symbolic attributes.